Source-sink behavioural dynamics limit institutional evolution in a group-structured society. Issue 3 (23rd March 2022) - Hébert-Dufresne, Laurent; Waring, Timothy M.; St-Onge, Guillaume; Niles, Meredith T.; Kati Corlew, Laura; Dube, Matthew P.; Miller, Stephanie J.; Gotelli, Nicholas J.; McGill, Brian J.
Abstract : Social change in any society entails changes in both behaviours and institutions. We model a group-structured society in which the transmission of individual behaviour occurs in parallel with the selection of group-level institutions. We consider a cooperative behaviour that generates collective benefits for groups but does not spread between individuals on its own. Groups exhibit institutions that increase the diffusion of the behaviour within the group, but also incur a group cost. Groups adopt institutions in proportion to their fitness. Finally, the behaviour may also spread globally. We find that behaviour and institutions can be mutually reinforcing. But the model also generates behavioural source-sink dynamics when behaviour generated in institutionalized groups spreads to non-institutionalized groups and boosts their fitness. Consequently, the global diffusion of group-beneficial behaviour creates a pattern of institutional free-riding that limits the evolution of group-beneficial institutions. Our model suggests that, in a group-structured society, large-scale beneficial social change can be best achieved when the relevant behaviour and institutions remain correlated.